FREQUENCY OF GENERALIZED ANXIETY DISORDER IN HOSPITALIZED COVID-19 PATIENT - SHAH, IU; AKHUNZADA, WA; RIAZ, Q; WAZIR, AH (Biological and Clinical Sciences Research Journal, 2024)
The COVID-19 pandemic has had a profound impact on mental health, with anxiety disorders being particularly prevalent among hospitalized patients. Identifying and addressing mental health issues like generalized anxiety disorder (GAD) is crucial for improving patient outcomes and providing holistic care. Objective: To determine the frequency of generalized anxiety disorder (GAD) among hospitalized COVID-19 patients at MTI-Hayatabad Medical Complex, Peshawar, and to explore its association with gender and socioeconomic status. Methods: A cross-sectional study was conducted in the Department of Psychiatry at MTI-Hayatabad Medical Complex, Peshawar, over six months, from October 16, 2021, to April 16, 2022. A total of 179 hospitalized COVID-19 patients, aged 25 years and above, were included. Patients presenting with symptoms of anxiety were assessed using the Generalized Anxiety Disorder-7 (GAD-7) scale. Unstable patients, who had a history of other mental disorders or were receiving treatment for depression and anxiety were excluded. Data were analyzed using statistical methods to explore associations between GAD and demographic factors such as gender and socioeconomic status. Results: The study included 179 COVID-19 patients, with a mean age of 43.50 ± 10.18 years. Generalized anxiety disorder was identified in 62 patients, representing 34.6% of the total population. GAD prevalence was significantly higher among female patients (p < 0.001) and those from lower socioeconomic backgrounds (p = 0.002). Conclusion: This study highlights a high prevalence of generalized anxiety disorder among hospitalized COVID-19 patients, particularly among females and those of lower socioeconomic status. The findings underscore the need for routine mental health screening and targeted interventions to address anxiety in this vulnerable population.